Government Public Relations and Social Media: Bridging the Digital Divide on People with Social Welfare Problems - Sri Haryanti; Effy Zalfiana Rusfian (Magister Administrasi Publik, 2018)
This study is a public relations inquiry that aims to describe the use of social media by govern-ment public relations to bridge the digital divide that affects people with social welfare prob-lems. The research, unlike most public relations studies that by and large, focus on organiza-tional image, reputation, communication crisis, and transparency, uses the digital divide per-spective. The research uses Grunig and Hunt Public Relations model and Melvin De Fleur com-munication model perspectives to examine the communication processes that occur through government public relations social media. The research uses a qualitative descriptive approach to assess the communication conducted by informants. The results showed that government pub-lic relations communication through social media has not been fully able to bridge the digital divide, especially in rural areas. The digital divide creates three relates problems that affect the effectiveness of government communication with people that experience social welfare problem. Firstly, pattern of communication involves opinion leaders. Secondly, most feedback occurs in-directly while ideally, it should be direct. Thirdly, the flow of information takes place in either one or two steps, in contrast with the ideal, which should be in one step.